Understanding the Link Between Discrimination and Juvenile Delinquency Among Chinese Migrant Children - Li, Spencer D. (Journal of contemporary criminal justice, 2018)
Prior research has identified discrimination as a cause of delinquency among migrant children. Few studies, however, have examined how discrimination is related to delinquency. The current research aims at bringing more understanding to this issue. Based on the general strain theory, this study posits that discrimination facilitates delinquent behavior because it reduces social support, generates negative emotions, and erodes social bonds. To test these hypotheses, this study collected survey data from a probability sample of 1,300 migrant children who attended secondary schools in one of the largest cities in China. Structural equation modeling analysis was conducted to test the direct and indirect effects of discrimination on delinquency. The results show that perceived discrimination reported by the students was positively related to delinquency through all three mediating mechanisms. This study suggests that strengthening social support may provide an effective strategy to reduce delinquency among migrant children in a short and intermediate term while ending discrimination represents a more long-term solution.